The Waterfall Fascia Lata Interposition Arthroplasty "Grika Technique" as Treatment of Posttraumatic Osteoarthritis of the Elbow in a High-Demand Adult Patient: Validity and Reliability. (22nd April 2018) - Rollo, Giuseppe; Rotini, Roberto; Eygendaal, Denise; Pichierri, Paolo; Prkic, Ante; Bisaccia, Michele; Lanzetti, Riccardo Maria; Lupariello, Domenico; Meccariello, Luigi
Abstract : Introduction . The elbow interposition arthroplasty is a very common procedure performed mainly on active young patients who need great functionality and for whom total joint replacement is contraindicated and arthrodesis is noncompliant. We are going to demonstrate a case of a 34-year-old male suffering from malunion of the distal humerus, elbow stiffness, and manifest signs of arthrosis of the dominant limb, treated with the IA Grika technique at a 5-year follow-up. Patients and Methods . The chosen criteria to evaluate the injured side and the uninjured side during the clinical and radiological follow-up were the objective function and related quality of life, measured by the Mayo Elbow Performance Score (MEPS), and postoperative complications. To assess flexion and supination forces and elbow muscular strength, a hydraulic dynamometer was used. Results . At a 5-year follow-up, the results were excellent as during the first year. Conclusions . The Grika technique is a valid and feasible option in the treatment of elbow injuries.